Influence of high-irradiance light curing on the marginal integrity of composite restorations in primary teeth - Janina Frank; Tobias T. Tauböck; Marcus Zimmermann; Thomas Attin; Blend Hamza (BMC, 2023)
Abstract Background Reducing the necessary time to restore primary teeth improves the cooperation of paediatric patients. This study aimed to investigate the marginal integrity of restorations prepared with a bulk-fill resin-based composite (RBC) containing additional fragmentation chain transfer (AFCT) compared to a conventional RBC when light cured with a rapid high-irradiance (3 s) and a regular (10 s) curing mode. Methods Forty class-II cavities were prepared in 40 primary molars. The molars were randomly divided into four groups based on the applied light-curing modes (regular: 10 s @ 1200 mW/cm2 or high-irradiance: 3 s @ 3000 mW/cm2) and the used restorative material (AFCT-containing bulk-fill RBC "Power Fill" or AFCT-free conventional RBC "Prime"). After thermo-mechanical loading, the marginal integrity was analysed using scanning electron microscopy. A beta regression model and pairwise comparisons were used to statistically analyse the data. Results The mean marginal integrity (% ± SD) of the restorations for each group was as follows: Power Fill (10 s: 79.7 ± 15.6) (3 s: 77.6 ± 11.3), Prime (10 s: 69.7 ± 11.1) (3 s: 75.0 ± 9.7). The difference between the RBCs for the same light-curing mode was statistically significant (p ≤ 0.05). The difference between the light-curing modes for the same RBC was not statistically significant (p ˃ 0.5). Conclusions AFCT-containing bulk-fill RBC "Power Fill" achieves similar marginal integrity when light-cured with either high-irradiance or regular light-curing modes. "Power Fill" achieves better marginal integrity than the conventional RBC "Prime" regardless of the applied light-curing mode.